The Indian contribution to the development of the history of South Africa. - Pachai, Bridglal (My University, 1974)
The historical context of time, place and circumstances helps to place the Indian factor in South African history in perspective. Within this context it is possible to periodize as well as to characterize this factor so as to identify its outstanding features in a convenient and meaningful way. The periods as well as their outstanding features may be listed as follows; 1860-1902, arrival and settlement; 1902-1910, beginnings of political mobilization; 1910-1924, a place in the new unified state; 1924-1948, an appeal to internal and external diplomacy; 1948—1974, accommodation on the basis of a permanent stake in the country. The chronology represents landmarks in South African history which were neither shaped nor influenced by the Indian factor which has always been limited by relative numerical insignificance as well as by economic and political restrictions. The first period ended with the establishment of British paramountcy; the second with the creation of Union; the third with the advent of Hertzogism and Afrikaner ascendancy; the fourth with the appearance of the Nationalist doctrine of Apartheid and the last with the contemporary scene of the balkanization of the South African peoples and polities.
African Studies Seminar series. Paper presented August 1974
Keywords: East Indians. South Africa; South Africa. Race relations; South Africa. History. 20th century; South Africa. Race relations. History